Expressive English Phrases in Modern British Fiction - Korolyova, E. I. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2016)
The article focuses on the expressive noun and verb phrases of the English language in some texts of modern British fiction. An analysis of the formal-structural, semantic, and functional aspects of the said constructions enables the author to reveal the expressive resources of the phrase as a non-communicative syntactic unit. It is established that the expressive function of this unit leads to a shift in its systemic features. Expressive meaning is conveyed in the utterance by a pragmatically motivated transformation of the phrase structure (i.e. formal shifts towards greater sign complexity or simplicity) as well as by the stylistic means and non-neutral lexical units of the language used on the phrase level. Compared to the syntactic and denotative meanings of the phrase, its expressive semantics proves to be secondary, but still it is functionally significant in the contexts analyzed. Works of modern British fiction show a considerable communicative and pragmatic potential of the expressive English phrases, which convey a wide range of emotions in verbal communication. The author also identifies the expressive phrase general linguistic functions (expression of emotion, emotional impact, nominative, cognitive, epistemological, and axiological functions), as well as textual functions (structural, and semantic).